Application of preventive measures to an underground: spectrum of unlimited questions - Rogatynska, Nina; Kolodijchuk, Nazar (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The research covers the peculiarities of the use of precautionary measures and their types in juvenile criminal proceedings. The problem issues are analyzed and the views of scientists, their approaches to the application of certain preventive measures to this population group are taken into account. The advantages and disadvantages of the use of preventive measures and other educational means in the legislation are indicated